SURVEI TINGKAT KEMAMPUAN FISIK ANGGOTA UNIT KEGIATAN MAHASISWA RESIMEN MAHASISWA 804 TAHUN 2017-2018 UNIVERSITAS NEGERI SURABAYA - wrediningsih, wuri; Sudijandoko, Andun (Jurnal Kesehatan Olahraga, 2019)
Abstract Physical condition is a whole of the components that cannot be separated easily, either upgrading or maintenance. It means that every effort in order to improve the physical condition have to develop all the components. The components of the physical conditions are: strength, endurance, speed, muscle explosive power, flexibility, agility, balance, coordination, accuracy, and reaction. The purpose of this study is to determine the level of physical ability of regiment student no 804 (i.g one of students organization) of Surabaya State University year 2017-2018. This research is descriptive quantitative research that uses survey as the method. The population of this research is 39 of the member of regiment student no 804 of Surabaya State University year 2017-2018. 39 samples taken by using purposive sampling technique. This research uses research instrument of Indonesian Army Kesamaptaan physical test. The result of the data analysis using manual calculation is known that the percentage of the level ability of physical condition of 39 member of regiment student no 804 years 2017-2018 Surabaya State University is in a good condition with the category of 0%, there are 2 members that are in a good category as 5,12%, which included to enough category as many as 16 members equal to 41,02%, which included in category less as many as 21 members equal to 53,8%, and that included in category less once 0%. Thus, it can be concluded that the survey of physical ability level of the regiment students no 804 of Surabaya State University year 2017-2018 has average value of 40.84 that is included in the category of enough (C). Keywords: Survey, Physical Condition, Regiment Students no 804